Risk of Ischemic Placental Disease in Relation to Family History of Preeclampsia - Ananth, Cande V.; Jablonski, Kathleen; Myatt, Leslie; Roberts, James M.; Tita, Alan T. N.; Leveno, Kenneth J.; Reddy, Uma M.; Varner, Michael W.; Thorp, John M., Jr; Mercer, Brian M.; Peaceman, Alan M.; Ramin, Susan M.; Carpenter, Marshall W.; Samuels, Philip; Sciscione, Anthony; Tolosa, Jorge E.; Saade, George; Sorokin, Yoram; for the National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2019)
Objective To assess the risk of ischemic placental disease (IPD) including preeclampsia, small for gestational age (SGA), and abruption, in relation to preeclampsia in maternal grandmother, mother, and sister(s).Study Design We performed a secondary analysis of data from a randomized trial of vitamins C and E for preeclampsia prevention. Data on family history of preeclampsia were based on recall by the proband. The associations between family history of preeclampsia and the odds of IPD were evaluated from alternating logistic regressions.Results Of the 9,686 women who delivered nonmalformed, singleton live births, 17.1% had IPD. Probands provided data on preeclampsia in 55.5% (n = 5,374) on all three family members, 26.5% (n = 2,562) in mother and sister(s) only, and 11.6% (n = 1,125) in sister(s) only. The pairwise odds ratio (pOR) of IPD was 1.16 (95% confidence interval [CI]: 1.00–1.36) if one or more of the female relatives had preeclampsia. The pORs of preeclampsia were 1.54 (95% CI: 1.12–2.13) and 1.35 (95% CI: 1.03–1.77) if the proband's mother or sister(s) had a preeclamptic pregnancy, respectively, but no associations were seen for SGA infant or abruption.Conclusion This study suggests that IPD may share a predisposition with preeclampsia, suggesting a familial inheritance.
Keywords: ischemic placental disease; preeclampsia; placental abruption; small for gestational age infant; family history; inheritance